Two new species of the genus Kapsa Dworakowska from the karst area of Southwest China (Hemiptera: Cicadellidae: Typhlocybinae) - Yang, Xiao; Luo, Guimei; Song, Yue-Hua (Zootaxa, 2022)
The leafhopper genus Kapsa Dworakowska, 1972 contains 32 species, mainly known from the Oriental Realm. Two new species collected from Huajiang Town, Guizhou Province, China are described and illustrated, Kapsa huajiangensis sp. n. and Kapsa uniaxialis sp. n. A key to distinguish all the Chinese species of the nominotypical subgenus is given.